2015
DOI: 10.1021/acs.energyfuels.5b01274
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Capture of CO2 by Ether-Functionalized Pyridinium Ionic Liquids with Low Viscosity

Abstract: In this work, three kinds of ether-functionalized pyridinium-based ILs [E n Py]­[NTf2] with low viscosity were designed and synthesized and used for highly selective separation of CO2 from CH4. It was found that the ether groups play an important role on physicochemical properties and CO2/CH4 selectivity in these three ILs. Compared with the nonfunctionalized analogues [C m Py]­[NTf2], the viscosities of [E n Py]­[NTf2] are lower and obviously decrease with the increasing number of ether oxygen atoms. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 45 publications
5
65
0
2
Order By: Relevance
“…The solubility of NH 3 in ILs was measured using vapor liquid equilibrium (VLE) apparatus as shown in Fig. , as had been used in previous work , . The system was composed of a cylinder, a gas reservoir, an absorption cell, a vacuum pump, pressure sensors and valves.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solubility of NH 3 in ILs was measured using vapor liquid equilibrium (VLE) apparatus as shown in Fig. , as had been used in previous work , . The system was composed of a cylinder, a gas reservoir, an absorption cell, a vacuum pump, pressure sensors and valves.…”
Section: Methodsmentioning
confidence: 99%
“…During recent decades, ionic liquids (ILs) have emerged as new solvents in the field of gas separations owing to their outstanding properties, such as high thermal stability, negligible vapor pressures and tunable structures. [14][15][16][17][18][19][20][21][22] Therefore, the NH 3 absorption by ionic liquids has aroused interest around the world, and researchers have paid a lot of attention to the screening and designing of ILs to increase NH 3 solubility along with good desorption performance. Yokozeki 2 ] as an example and explained that hydrogen atoms of the cation played an important role in NH 3 absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Task-specic ionic liquids (TSILs), also called functionalized ionic liquids, can improve the CO 2 absorption capacity and the absorption selectivity by introducing suitable moieties (like amine, 26,27 ether, 28 and nitrile groups 29 ) to ILs. [30][31][32] Considered the hydroxyl groups and the ether groups in cellulose acetate (CA), etherfunctionalized pyridinium-based ILs should be compatible with CA, which can be benecial for improving CO 2 separation performance. Moreover, ILs with pyridinium cations are relatively cheaper, more biodegradable, and less toxic compared with imidazolium-based ILs.…”
Section: Introductionmentioning
confidence: 99%
“…The density value of the mixed absorbents was between the density value of 30 22,34 while the viscosity of the absorbents was below 10 mPa s with n I of 0-0.6, which showed that the addition of 30 vol% solution reduced the viscosity of absorbents signicantly. According to Fig.…”
Section: Physical Properties Of the Investigated Solventsmentioning
confidence: 87%